PROGRAM PENDAMPINGAN MAKANAN SEHAT DAN BERGIZI PADA WARGA KAMPUNG SARMAYAM DISTRIK TANAH MIRING KABUPATEN MERAUKE - Rosmala Widijastuti; Sunarni Sunarni; Wahida Wahida (Musamus University, 2021)
The spread of the Covid 19 virus in 2019 and continuing in 2020 has made all members of thecommunity remain vigilant in maintaining public and individual health. Public understanding onhow to prevent the spread of the virus through health protocols have been implemented in aconscious manner. Apart from protect themselves through avoiding physical contact, people arealso obliged to know how to protect themselves through improving their own health status(immunity), one of which is through food. Processed foods that are consumed every day haveadvantages and disadvantages to meet their balanced nutritional needs. This community serviceis carried out with the aim of providing solutions in making processed food that can improvepeople immunity and thus prevent the spread of the Covid 19 virus. The method of implementingthis service activity through theory and practice is carried out on community members, especiallyPKK member in Sarmayam village, amounting to 30 people. The activity is carried out for oneday at the Sarayam village hall. The result of this activity is that the community understand whyand how the Covid 19 virus can be transmitted, then the community can make healthy food intakein the form of processed food to meet nutritional needs during the Covid 19 pandemic. Skills andknowledge have increased related to understanding healthy food processing. and nutritious.